Hydranencephaly: a rare case report on enlarging head in an infant - Vishnoi, Dakshata; Rathoria, Ekansh; Dutta, Gaurav; Aalam, Shaik; Shukla, Nalin; Singh, Jitendra Kumar (International Journal of Scientific Reports, 2025)
Hydranencephaly is an uncommon congenital disorder in which the cerebral hemispheres are absent and replaced by cerebrospinal fluid. In this article, we describe an uncommon case of hydranencephaly in a 3-month-old male child with complaints of progressively increasing head size over the last 1 month and inability to control his neck. The child was diagnosed as a case of Hydranencephaly by cranial ultrasonography (USG) and further confirmed by computed tomography (CT) and magnetic resonance imaging (MRI) which revealed a complete absence of the cerebral hemisphere with intact falx, brain parenchyma was replaced by a sac-like structure containing CSF, reduced volume of the midbrain, and a thin rim of brain tissue was seen at the frontal and temporal region bilaterally and at the lateral aspect of the falx cerebri. The child was managed using a ventriculoperitoneal shunt procedure. Hydranencephaly requires prompt diagnosis using Cranial USG, CT, or MRI and treatment by ventriculoperitoneal shunt procedure and a multi-disciplinary approach. Proper parental counselling is required as it has a bad prognosis.